2014
DOI: 10.1038/pr.2014.48
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines associated with necrotizing enterocolitis in extremely-low-birth-weight infants

Abstract: Background The goal was to identify cytokines associated with necrotizing enterocolitis (NEC). Based on our earlier reports of decreased tissue expression of transforming growth factor (TGF)-β, we hypothesized that infants with NEC also have low blood TGF-β levels. We further hypothesized that because fetal inflammation increases the risk of NEC, infants who develop NEC have elevated blood cytokine levels in early neonatal period. Methods Data on 104 extremely low birth weight (ELBW) infants with NEC and 893… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
119
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 40 publications
11
119
0
1
Order By: Relevance
“…It should be noted that the most pronounced therapeutic effect was achieved after multiple infusions of these cells. The results support the expectations of several experts who have recently proposed [44] that "an allogeneic 'off-theshelf' product . would make UCB cellebased intervention available to all infants and children in need of this therapy."…”
Section: Resultssupporting
confidence: 89%
“…It should be noted that the most pronounced therapeutic effect was achieved after multiple infusions of these cells. The results support the expectations of several experts who have recently proposed [44] that "an allogeneic 'off-theshelf' product . would make UCB cellebased intervention available to all infants and children in need of this therapy."…”
Section: Resultssupporting
confidence: 89%
“…Previous studies have shown that no correlation exits between plasma IL-10 level and NEC severity, and plasma IL-1β, IL-6, and IL-8 are generally not detectable [12,13]. This contrasts with results from infants, where elevated IL-1β, IL-6, IL-8, and IL-10 levels have been observed in NEC patients [25,26]. It is therefore important to be critical when inflammatory mediators are used as biomarkers of NEC, and the results may vary according to biological target (mRNA or protein), sample type (plasma or gut tissues), and species (humans, pigs, or rodents).…”
Section: Discussionmentioning
confidence: 92%
“…SIRS, systemic inflammatory response syndrome; HRC, heart rate characteristics. recent report of over 900 preterm infants indicates that low serum levels of transforming growth factor-beta in the first days after birth are associated with development of NEC [16].…”
Section: Risk Assessment For Sepsis and Necmentioning
confidence: 99%